ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI EKSPOR BIJI KAKAO (Theobroma cacao) KERING (STUDI KASUS PADA PTPN XII (PERSERO) KEBUN NGRANGKAH PAWON- KEDIRI, JAWA TIMUR) - Farah Mutiara (Universitas Islam Madura, 2016)
Cocoa is one of the important agricultural products in Indonesia. Currently, Indonesiaranks third after Ivory Coast and Ghana as the world’s largest cocoa producer. In Indonesia, the cocoa type that can be grown is a kind of cocoa Bulk. There are many kinds of government and private sector that work in this cocoa commodity as both upstream or downstream. PTPN XII (Persero) Ngrangkah Pawon Plantation is one of company that work in the same field, in this means cocoa. This study objectives are: 1)To analyze the export trend of cocoa beans in PTPN XII (Persero) Ngrangkah Pawon Plantation, 2)To analyze the factors that affecting export of cocoa beans in PTPN XII (Persero) Ngrangkah Pawon Plantationand, 3)To analyze the benefits of cocoa beans in PTPN XII (Persero) Ngrangkah Pawon Plantation. Theresearchmethoduse trend analysisto analyze the export trend, use multiple linear regression to analyze the factors that affecting export volume of cocoa and use cost-benefit analysis to analyze thebenefit of cocoa beans. The analysisstates thatthe export trend in research location have a decrease movement pattern, factors that affecting on export volume of cocoa beans is production of cocoa beans in research locationandthe agribusiness of cocoa beans in Ngrangkah Pawon is profitable. Hopefully, with this conditions the related institution would consider all decision about cocoa in order to increase the export volume dan profitable of cocoa itself.